Anatolia at the Core of Russia-West Rivalry and Soviet Policy of Ankara Government - Ada, Turhan (TURK TARIH KURUMU, 2018)
Anatolian Ankara, in the period of the National Struggle, wanted to neutralize Western imperialism with Soviet support, taking advantage of the competition between the West and Russia. With this strategy, it was not only aimed at achieving military success with Soviet assistance, but also at the same time, in Western capitals, by establishing a fear of Bolshevik Anatolia, the Entente States confirmed the existence of Independent Anatolia. Likewise, although the Soviets knew such a possibility, they were willing to accept an independent Anatolia, even if they were not Bolsheviks, and they were seriously concerned about possible Western influence in the region. Thanks to these two dynamics, Ankara has started advantageously and has always maintained this position. As a result, a precarious conjuncture was formed with the forced cooperation of the two chambers that cooperated against the common enemies by enforcing the conditions. Ankara and Moscow have seen each other as a compulsive partner ready to drop themselves at any moment. Of course, the most worrying party in this context was Ankara, which identifies such a possibility with prisoner, and kept Ankara on an ethical, problem-free basis, since this possibility is also valid for Moscow In the last scene of the process, the Turkish victory was determined, and Ankara, which evaluated the advantage with military power, succeeded. Entente States and Moscow have accepted an Anatolia which is independent of each other.
Keywords: Ataturk; War of Independence; Foreign Policy; Soviet Russia; Treaty of Moscow; Archaeology; History